KEBIJAKAN UTANG PUBLIK DALAM EKONOMI ISLAM: ANTARA KEBUTUHAN NEGARA DAN PRINSIP KEADILAN ANTAR GENERASI - Deswita Lestari Batubara; Balqis Nurul Jannah; Reihansyah Azdi Bintang (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
Public debt is one of the important instruments in state financing; however, its implementation must consider intergenerational justice, particularly from the perspective of Islamic economics. This article discusses how public debt policy can balance the urgent needs of the state for development with the principle of justice that prevents excessive burdens on future generations. By referring to Sharia principles, such as the prohibition of riba (usury), transparency, and efficient use of resources, this study emphasizes the importance of productive and sustainable public debt. The findings indicate that the implementation of Sharia-compliant financial instruments, careful fiscal management, and long-term planning are key to aligning the state's development needs with moral responsibility toward future generations. This approach is expected to provide guidance for formulating fiscal policies that are fair, sustainable, and in accordance with the values of Islamic economics.